Structure-activity relationships of 2-benzylsulfanylbenzothiazoles: synthesis and selective antimycobacterial properties - Klimešová, Vĕra; Kočí, Jan; Palát, Karel; Stolaříková, Jiřina; Dahse, Hans-Martin; Möllmann, Ute (Medicinal chemistry, 2012)
A set of 2-benzylsulfanyl derivatives of benzothiazole was synthesized and evaluated for antimicrobial and cytotoxic activities. The biological screening on antimicrobial activity against a panel of Gram-positive and Gram-negative bacteria, yeasts and fungi identified benzylsulfanyl derivatives of benzothiazole as selective inhibitors of mycobacteria. The lead compounds in the set, dinitro derivatives exhibited significant activity against sensitive and multidrug-resistant strains of M. tuberculosis and low cytotoxicity. The QSAR study indicated that the antituberculotic activity is connected with LUMO and HOMO energies. The lower lipophilicity and the increased size of the molecule contribute to antituberculotic activity. Thus, dinitrobenzylsulfanyl derivatives of benzothiazole represent promising smallmolecule synthetic antimycobacterials.
Keywords: HeLa Cells; Benzothiazoles; Sulfides; proliferace buněk; vztah mezi dávkou a účinkem léčiva; Mycobacterium tuberculosis; sulfidy; mikrobiální testy citlivosti; Cell Line, Tumor; Quantitative Structure-Activity Relationship; screeningové testy protinádorových léčiv; benzothiazoly; Structure-Activity Relationship; lidé; HeLa buňky; Antineoplastic Agents; protinádorové látky; Anti-Bacterial Agents; Humans; Microbial Sensitivity Tests; Dose-Response Relationship, Drug; Cell Proliferation; vztahy mezi strukturou a aktivitou; Drug Screening Assays, Antitumor; antibakteriální látky; nádorové buněčné linie; kvantitativní vztahy mezi strukturou a aktivitou